Effect of oral administration of gabapentin on the minimum alveolar concentration of isoflurane in cats - Chen, Hangbin; Yang, Huan; Li, Mengqing; Peng, Haojie; Guo, Weibin; Li, Meng (Frontiers in Veterinary Science, 2023)
Objective To determine if oral gabapentin decreases the minimum alveolar concentration (MAC) of isoflurane in cats. Study design Prospective, randomized, blinded, crossover, experimental study. Animals A total of six healthy adult cats (3 male, 3 female) aged 18-42 months, weighing 3.31 ± 0.26 kg. Methods Cats were randomly given oral gabapentin (100 mg cat-1) or placebo 2 hours before starting MAC determination, with the crossover treatment given at least 7 days apart. Anesthesia was induced and maintained with isoflurane in oxygen. Isoflurane MAC was determined in duplicate using an iterative bracketing technique and tail clamp method. Hemodynamic and other vital variables were recorded at each stable isoflurane concentration and were compared between gabapentin and placebo treatments at lowest end-tidal isoflurane concentration when cats did not respond to tail clamping. A paired t test was used to compare normally distributed data, and a Wilcoxon signed-rank test was applied for non-normally distributed data. Significance was set at p < 0.05. Data are mean ± standard deviation. Results Isoflurane MAC in the gabapentin treatment was 1.02 ± 0.11%, which was significantly lower than that in the placebo treatment (1.49 ± 0.12%; p < 0.001), decreasing by 31.58 ± 6.94%. No significant differences were found in cardiovascular and other vital variables between treatments. Conclusion and clinical relevance Oral administration of gabapentin 2 hours before starting MAC determination had a significant isoflurane MAC-sparing effect in cats with no observed hemodynamic benefit.